The Implementation of Teachers’ Roles in Teaching English for Inclusive Students - Nurcholis, Ivan Achmad; Sari, Rini Puspita; Safitri, Washlurachim; Ananda, Ririn Putri (Universitas Pahlawan Tuanku Tambusai, 2024)
The primary objective of this study was to explore how teachers' roles are put into practice when teaching English to inclusive students at Elementary Schools in Bengkulu City. The research followed a descriptive qualitative approach in its design. The study involved 7 English teachers who were responsible for instructing English at various Elementary Schools in Bengkulu City, namely SDN 03, SD Al-Manar, SD Alam Mahira, SDN 61, SDN 73, SDN 24, and SD Al-Aufa. To gather data, the researchers employed an observation checklist and an interview guide. The observation checklist used in this study was adapted from Tyagi's work in 2016. There are 5 teachers’ roles in teaching inclusive students that were observed by the researcher which consisted 14 items. The research finding indicated that there were five teachers’ roles in teaching inclusive students at Elementary Schools in Bengkulu city, namely; teacher role as corrector, inspirator, culminator, facilitator, and evaluator. There were 71% of teachers implemented corrector and inspirator, there were 65% of them implemented teacher role as culminator, 24% as facilitator, and 100% of teachers applied teacher role as evaluator. The researcher suggested for English teachers to implement teacher role as facilitator since less than fifty percent of English teachers who implemented teacher role as facilitator.